المقاربة النظرية لإحدى سمات الشخصية المناعية : الصلابة النفسية - بلوم, محمد; حنصالي, مريامة (Sciences de l'Homme et de la Société; Vol. 8 (2013): SCIENCES DE L'HOMME ET DE LA SOCIÉTÉ, 2014)
اتخذ علم النفس منذ ظهور الاتجاه الإنساني منحى آخر في البحث ركز من خلاله على الإنسان بوصفه صيرورة متواصلة من النماء تميزها القيم و الفضائل الإنسانية النابعة من طبيعته الخيرة، و تجسد الصلابة النفسية في جوهرها معاني تلك القيم و الفضائل.وتعد الصلابة النفسية إحدى سمات الشخصية التي تسهم في الحفاظ على الصحة النفسية و الجسدية، إذ تعمل على تعديل استجابة الضغط المناعية للجسم مشكلة بذلك عاملا وسيطا بين الضغوط و الصحة. هدف المقال هو تسليط الضوء على المقاربات النظرية التي تناولت الصلابة النفسية بالتفسير قصد إبراز نقاط التقاطع التي تشترك فيها تلك المقاربات و التوجهات لإعطاء نظرة تكاملية توضح سمة هامة من سمات الشخصية المناعية. Since the advent of the humanistic trend, psychology took another orientation in research, through which it focused on the human being, describing him as a continuous developmental process distinguished by humanitarian values and virtues stemming from his good nature . As to the concept of psychological hardiness it embodies in it's essence the meanings of these values and virtues. Psychological hardiness is one of the personality traits that contribute to maintaining mental and physical health, as it works on modulating the body's immune stress response, thus representing an intermediary factor between stress and health.The aim of this paper is to shed light on the theoretical approaches that dealt with psychological hardiness, in order, to highlight the points of intersection in common with these approaches and trends, and to provide an integrative view that clarifies an important feature among features of the immune personality.